Sonogenerated metal-hydrogen sponges for reactive hard templating1. Issue 36 (4th May 2015) - Baidukova, Olga; Möhwald, Helmuth; Mazheika, Aliaksei S.; Sviridov, Dmitry V.; Palamarciuc, Tatiana; Weber, Birgit; Cherepanov, Pavel V.; Andreeva, Daria V.; Skorb, Ekaterina V.
<x xml:space="preserve">Abstract</x> Sonogenerated magnesium-hydrogen sponges with low dehydrogenation energy are used as prospective reactive hard templates for the synthesis of organized nanostructures.